2014
DOI: 10.1002/embr.201338144
|View full text |Cite
|
Sign up to set email alerts
|

The presequence pathway is involved in protein sorting to the mitochondrial outer membrane

Abstract: The mitochondrial outer membrane contains integral a-helical and b-barrel proteins that are imported from the cytosol. The machineries importing b-barrel proteins have been identified, however, different views exist on the import of a-helical proteins. It has been reported that the biogenesis of Om45, the most abundant signal-anchored protein, does not depend on proteinaceous components, but involves direct insertion into the outer membrane. We show that import of Om45 occurs via the translocase of the outer m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
62
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(64 citation statements)
references
References 34 publications
2
62
0
Order By: Relevance
“…One possibility is that the reduced PC levels affect the function of the TOM complex. However, the accumulation of TIM23-dependent precursors like Om45-DHFR (81,82) and Oxa1 at the TOM complex was not decreased (Fig. 6B) (75).…”
Section: Depletion Of Pc Impairs Protein Transport Into the Innermentioning
confidence: 92%
“…One possibility is that the reduced PC levels affect the function of the TOM complex. However, the accumulation of TIM23-dependent precursors like Om45-DHFR (81,82) and Oxa1 at the TOM complex was not decreased (Fig. 6B) (75).…”
Section: Depletion Of Pc Impairs Protein Transport Into the Innermentioning
confidence: 92%
“…The yeast strain expressing Por1 HA in the YPH499 background was generated by chromosomal integration of a coding region for a triple HA tag and a HIS3 cassette in front of the stop codon of POR1 by homologous recombination (22). Yeast cells were grown on yeast extract/peptone/glycerol medium (1% (w/v) yeast extract, 2% (w/v) bactopeptone, 3% (v/v) glycerol) at 24 -30°C.…”
Section: Methodsmentioning
confidence: 99%
“…After excessive washing with digitonin buffer containing 0.1% (w/v) digitonin, bound proteins were eluted under native conditions by incubation with 1 mg/ml HA peptides (Roche Diagnostics). Tom22 His -containing protein complexes were purified by nickel in complex with nitrilotriacetic acid-agarose (Qiagen, Germany) (22). Denatured proteins were analyzed by SDS-PAGE, and native samples were subjected to BN-PAGE.…”
Section: Methodsmentioning
confidence: 99%
“…Yeast Strains and Growth Conditions-The yeast wild-type strains YPH499, YPH499 arg4⌬, and JK9 -3d (the wild type for hsp10ts and hsp60ts); the wild-type strain for ssc1-42; and the mutant strains mtHsp70 His , ssc1-42, hsp10ts, and hsp60ts have been described before (39,44,54). For SILAC-based mass spectrometric analysis of mtHsp70 His purification, a kanMX4 cassette was integrated into the ARG4 locus by homologous recombination in the yeast strain expressing mtHsp70 His .…”
Section: Methodsmentioning
confidence: 99%
“…So far, it has been reported that mtHsp70 is required for the import of Hsp60, but a potential role of the chaperone in the formation of Hsp60 complexes has not been addressed (43). To distinguish between the role of mtHsp70 in import or folding and assembly of the Hsp60 precursors, we used a temperature-sensitive mutant of mtHsp70, ssc1-42 (54). The ssc1-42 mutant mtHsp70 harbors six point mutations that are distributed randomly in the ATPase, substrate-binding, and C-terminal domains of the chaperone (I101T, I114N, I485L, N560D, V588A, and K626R).…”
Section: Mthsp70 Promotes the Formation Of Hsp60mentioning
confidence: 99%